Touchscroll Keyboard Bimanual Scrolling Concept - Usability Report - Hinckley, Ken (2000)
The TouchScroll Keyboard Bimanual Scrolling Concept study was conducted in three rounds on June 13-14, June 29-30, and July 20, 2000. This was initial informal testing and design iteration of a touch-sensitive scrolling strip integrated with the keyboard. Each round included 5 participants of intermediate to advanced computer skills, each group consisting of 3 women and 2 men. A greater proportion of women than men was included in the study because it was anticipated that more problems might arise with sensing women’s fingers (long fingernails, hand lotions). The study included 3 lefthanders (one in each round), although only one of these subjects used the mouse in the left hand (this subject was in the first round of 5 subjects).